ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP KELAS VII PADA MATERI PERSEGI PANJANG - Rika Kartika; Euis Eti Rohaeti; M Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This descriptive qualitative research aims to describe the students' mathematical problem-solving abilities on the rectangular material for students of grade VIII SMP. The subjects in this study were students who were selected at random. The technique of collecting data using problem test technique. The type of test in this study is a description test. Most students have not been able to answer the problem maximally. Based on the results of tests that have been done the average percentage of test results about 60% of the description is still low. Still far from the expected researcher is 75%. Data analysis is done to analyze the extent of students' mathematical problem-solving abilities.